Intrinsic anti-inflammatory nanomedicines for enhanced pain management - Qiao, Bin; Yao, Jiaqian; Fan, Yu’ang; Zhang, Na; Feng, Miao; Zhao, Jiaju; Song, Xinye; Luan, Yong; Zhuang, Bowen; Zhang, Nan; Xie, Xiaoyan; Xu, Ming (Frontiers in Bioengineering and Biotechnology, 2024)
IntroductionEffective postoperative pain management remains a significant challenge due to the severe side effects of opioids and the limitations of existing analgesic delivery systems. Inflammation plays a critical role in pain exacerbation, highlighting the need for therapies that combine analgesic effects with intrinsic anti-inflammatory properties.MethodsHerein, we develop an intrinsic anti-inflammatory nanomedicine designed to enhance pain management by integrating controlled anesthetic release with inherent anti-inflammatory activity. Our nanoplatform utilizes dendritic mesoporous silica nanoparticles (MSNs) loaded with levobupivacaine and coated with Rg3-based liposomes derived from ginsenoside Rg3, termed LMSN-bupi.ResultsThe MSNs enable sustained and controlled release of the local anesthetic, while the Rg3-liposome coating provides intrinsic anti-inflammatory effects by inhibiting macrophage activation. In animal models, LMSN-bupi demonstrates significantly prolonged analgesic effects and attenuated inflammatory responses compared to traditional liposome-decorated nanoparticles (TMSN-bupi) (n = 5).DiscussionThese findings underscore the potential of intrinsic anti-inflammatory nanomedicines in enhancing pain management, offering a promising strategy to overcome the limitations of current therapies and improve patient outcomes in postoperative care.